In vitro long-term exposure to chlorhexidine or triclosan induces cross-resistance against azoles in Nakaseomyces glabratus - Kathrin Spettel; Dominik Bumberger; Richard Kriz; Sarah Frank; Madita Loy; Sonia Galazka; Miranda Suchomel; Heimo Lagler; Athanasios Makristathis; Birgit Willinger (Antimicrobial Resistance and Infection Control, 2025)
Abstract Background Topical antiseptics are crucial for preventing infections and reducing transmission of pathogens. However, commonly used antiseptic agents have been reported to cause cross-resistance to other antimicrobials in bacteria, which has not yet been described in yeasts. This study aims to assess the in vitro efficacy of antiseptics against clinical and reference isolates of Candida albicans and Nakaseomyces glabratus, and whether prolonged exposure to antiseptics promotes the development of antifungal (cross)resistance. Methods A high-throughput approach for in vitro resistance development was established to simultaneously expose 96 C. albicans and N. glabratus isolates to increasing concentrations of a given antiseptic – chlorhexidine, triclosan or octenidine. Susceptibility testing and whole genome sequencing of yeast isolates pre- and post-exposure were performed. Results Long-term exposure to antiseptics does not result in the development of stable resistance to the antiseptics themselves. However, 50 N. glabratus isolates acquired resistance to azole antifungals after long-term exposure to triclosan or chlorhexidine, revealing newly acquired mutations in the PDR1 and PMA1 genes. Conclusions Chlorhexidine as well as triclosan, but not octenidine, were able to introduce selective pressure promoting resistance to azole antifungals. Although we assessed this phenomenon only in vitro, these findings warrant critical monitoring in clinical settings. Graphical Abstract